English Bilingual Education: The Challenge Of Communication And Cognition Aspects Of Content Language Integrated Learning (CLIL) In Indonesia - Hapsari, Astri (English Education Department, Universitas Islam Indonesia, 2012)
This essay analyses the challenge of the implementation of Content Language Integrated Learning (CLIL) in the curriculum framework in Indonesia. Review on related literature and research findings support the arguments that the implementation of CLIL brings about the issues in cognition and communication aspects. Unless more appropriate English language education and more educational linguistic research are established, the implementation of CLIL should be reconsidered.Key words: English bilingual education, CLIL, Indonesia